Toward an EU Gas-Purchasing Cartel - Peter Cramton; François Lévêque; Axel Ockenfels; Steven Stoft (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
"Instead of outbidding each other and driving prices up," on 25 March, the 27 EU nations decided to "pool [their] purchasing power" for the "voluntary common purchase of gas". In short, they decided to form a buyers' cartel. So far, difficulties have been identified, but what is needed is a systematic design effort addressing those difficulties. This column proposes a simple, but fairly comprehensive framework for an EU gas-purchasing cartel.
Keywords: 330